What's math got to do with it? : how teachers and parents can transform mathematics learning and inspire success - Boaler, Jo. (b)
A critical read for teachers and parents who want to improve children's mathematics learning. Featuring all the important advice and suggestions in the original edition of, this revised edition is now updated with new research on the brain and mathematics that is revolutionizing scientists' understanding of learning and potential. --Publisher's description
Includes index.
Keywords: Mathematics Study and teaching